EKSTRAKSI DAN KARAKTERISASI PIGMEN DARI KULIT BUAH RAMBUTAN (Nepheliumla ppaceumy) ar. BINJAI - Tri Susant, Lydia-, Simon B. Widjanarko, (Widya Mandala Surabaya Catholic University, 2001)
Rambutan fruits (Nephelium lappaceum) is one of tropical fruit having red coloured rinds, which may be due to anthocyanins content. This research was focused on finding optimal concentration of ethanol as solvent in the extraction of colouring matters and characterization of its properties. Two phases of laboratory works were carried out, first was concentration for extraction (70, 75, 80, 85, 90 and 95%), second was characterization of colouring matters affected by pH, heating, temperature, oxidator-reductors etc. Results of these experiments showed that 95% ethanol was the right concentration for extraction of colouring matters having maximal absorbancy of 0,24; pH of 1,06; anthocyanin concentration of 4,1 x 10-3 mg/ml; rendement of 13,67%. Characters of anthocyanin as follows : (1) Absorbancy at 30oC was 0,95 and at 100oC was 0,75 (2) Heated for 1 hour and 2 hours at 100oC resulting in absorbancy 0f 0,73 and no absorbancy, respectively (3) Reduction of absorbancy due to increase in pH absorbancy of 0,75; 0,31 and no absorbancy at the pH of 3; 4; 5 respectively (4) Effect of reductor after 12 hours storage producing absorbancy of 0,52 (5) Effect of lectric light for 24 hours showing absorbancy of 0,30, while 0,35 due to sunlight (6) Storage in cool room (15oC) for 7 days showing higher absorbancy of 0,24 compared to 0,09 stored in room temperature.